Amplification and cloning of exon regions from 1-4 of cathepsin B-like cysteine protease gene of Haemonchus contortus and immune response in lambs against cathepsin B-like cysteine protease fraction - PATHAK, CHARU; GHOURI, S K; KUMAR, S K; SAXENA, M M (The Indian Journal of Animal Sciences, 2015)
Haemonchus contortus is an economically important, highly pathogenic blood-sucking nematode parasite of ruminants. A study was conducted to characterize the cathepsin B-like cysteine protease gene of H. contortus of Indian origin, which has been explored as potential target for vaccine development. Adult H. contortus worms were collected from the abomasum of sheep and goats and whole genomic DNA was extracted and amplified using appropriate primers. The expected amplicon of 767 bp was cloned into T-vector using GeNeiTM Instant cloning kit. Immunization study was conducted to examine the effect of cysteine protease fraction on the faecal egg counts in lambs. It was found that the egg per gram of faeces was lower in immunized group as compared to control group (at 10, 11, 12, and 15 week). At post mortem, the worms recovered from the abomasa were lower in immunized group (800.40±101.8) as compared to control group (950.93±300.29). The results indicated that the immunization with cysteine protease fraction in lambs reduces the faecal egg count, but did not remove all the worms from lambs.